Solidarność . biuletyn KZ NSZZ "Solidarność" Huta Baildon-Katowice, no. 16, 1981 - [ed. Ryszard Pabiś et al., ill. Andrzej Mleczko] (KZ NSZZ "Solidarność" Huta Baildon, 1981)
Creation and circulation: For organizational use; Logo: BHH